2018
DOI: 10.1093/mnras/sty274
|View full text |Cite
|
Sign up to set email alerts
|

Particle content, radio-galaxy morphology, and jet power: all radio-loud AGN are not equal

Abstract: Ongoing and future radio surveys aim to trace the evolution of black hole growth and feedback from active galactic nuclei (AGN) throughout cosmic time; however, there remain major uncertainties in translating radio luminosity functions into a reliable assessment of the energy input as a function of galaxy and/or dark matter halo mass. A crucial and long-standing problem is the composition of the radio-lobe plasma that traces AGN jet activity. In this paper, we carry out a systematic comparison of the plasma co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 47 publications
(88 reference statements)
10
123
1
Order By: Relevance
“…This is illustrated in the right panel of Fig 18. The turbulent dissipation of energy within low Mach number jets was postulated by Bicknell (1985) and is clearly relevant to the radio structure of lowpowered radio galaxies. However, it is also established that FR I jets are intrinsically different in composition: -it is not just a matter of Mach number (Croston et al 2018). In addition, the jet speed itself is a potential factor as discussed fro the compact FR 0 sources by Baldi et al (2019), It is conjectured that mechanical feedback from active galactic nuclei is a key process in the evolution of galaxy clusters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This is illustrated in the right panel of Fig 18. The turbulent dissipation of energy within low Mach number jets was postulated by Bicknell (1985) and is clearly relevant to the radio structure of lowpowered radio galaxies. However, it is also established that FR I jets are intrinsically different in composition: -it is not just a matter of Mach number (Croston et al 2018). In addition, the jet speed itself is a potential factor as discussed fro the compact FR 0 sources by Baldi et al (2019), It is conjectured that mechanical feedback from active galactic nuclei is a key process in the evolution of galaxy clusters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FR II sources are generally more luminous than FR I sources (Fanaroff & Riley 1974;Ledlow & Owen 1996), though this distinction is not absolute . And lastly, it has been shown that the internal composition radio-lobe plasma is systematically different in these two types of radio galaxies (Croston et al 2018); the particle content of FRI lobes is dominated by protons and ions, whereas FRIIs are primarily composed of an electron-positron plasma.…”
Section: Radio Morphology 31 Classificationmentioning
confidence: 99%
“…An additional complication in using radio observational data to test physical models for jet dynamics and the FR divide is the weak relationship between jet power and radio luminosity. In particular, a systematic difference in the efficiency of producing radio luminosity for a given jet power for FRIs and FRIIs is thought to exist (Croston et al 2018), caused by the correlation of FR class with lobe particle content. FRI radio galaxies are found to be energetically dominated by heavy particles (protons and ions), while FRII radio galaxies are primarily composed of an electron-positron plasma (Croston et al 2018) -this situation may be best explained by the role of entrainment of surrounding material into disrupted FRI jets as they decelerate, while undisrupted FRII jets remain more "pristine".…”
Section: Introductionmentioning
confidence: 99%